Unheimliches Mauthausen. Zu Lydia Haiders Romanen - Jabłkowska, Joanna (Studia Germanica Posnaniensia, 2020)
Lydia Haider, is a young Austrian writer, whose work is in line with two tendencies characteristic for Austrian Literature. Haider describes Austrian province from a position of critical distance, focusing on the critique of language and attempts to thematize the lack of reckoning with national socialist past in specific Austrian contexts. The article analyses two novels by Haider: congregation and rotten. The novels foreground the discussion on the denial of the Nazi crimes on the lands surrounding Mauthausen Concentration Camp. The main question posed in the article is whether Haider could be called a inheritor of the critical “Heimatliteratur”. It is also important to investigate whether the young author offers new aesthetic solutions, adequate for contemporary perspective from which we can view the unsettled Nazi past.